Analisis Harga Lahan Di Wilayah Centeral District Bussines Baru Di Yogyakarta - Rifki Khoirudin; Gea Dwi Asmara (Jurnal Simki Economic, 2022)
The development of educational establishments in Yogyakarta is going very rapidly. The existence of Campus 4 of Ahmad Dahlan University has led to the development of economic activities around the area. Therefore, high activity and rapid development around the area have an impact on increasing land prices. This increase in land prices is accompanied by land conversion from agricultural, plantation, moorland, and vacant land to built-up land, which indirectly affects the physical development of the area. This research is a quantitative descriptive study which explains the relationship between land area, distance of land to campus, distance of land to main road, and road width in front of land to land prices in the area around Campus 4 of Ahmad Dahlan University. The research data were collected through interview methods, field observations, documentation, and literature study. The analysis tool used is multiple regression analysis. The results of this study indicate that the distance from the land to the campus and the width of the road in front of the land have an effect on land prices. Meanwhile, the land area and the distance from the land to the main road have no effect on land prices.